The Response of Microfertilizer Compound Application On Shallot Growth Result (Allium ascalonicum L.) var. Super Philip - Novelyn, Ruth; Setiawan, Adi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Brawijaya, 2025)
Shallots (Allium ascalonicum L.) are annual horticultural plants that have layered bulbs, fibrous roots, hollow cylindrical leaves and have an important role in the economy. The cause of the problem of decreasing shallot production results is due to the lack of knowledge of farmers who use chemical (inorganic) fertilizers incorrectly in the dosage used in shallot cultivation. The aim of this research is to determine the response to shallot growth results when using fertilizer with micro content. This research was conducted from October 2023 until January 2024 located in Semanding Village, Dau District, Malang Regency, East Java. This research used a Randomized Block Design (RBD) consisting of no fertilizer, 100% farmer treatment, 100% farmer treatment with 25% micro compound dose, 100% farmer treatment with 50% micro compound dose, 100% farmer treatment with 75% micro compound dose, 100% farmer treatment with 100% micro compound dose, 100% farmer treatment with 125% micro compound dose, 100% farmer treatment with 150% micro compound dose. The data obtained were analyzed using Analysis of Variance (ANOVA) at the 5% level and if there was a significant effect, the Duncan Multiple Range Test (DMRT) was carried out at the 5% level. The research results showed that giving 100% of the farmer treatment with 125% micro dose was able to increase plant growth and yield variables. However, this treatment had no effect on dry weight of leaves and roots, dry weight of total plant dry weight, and harvest index.